Cyanophycean Flora 0f Southern Himanchal Pradesh, India - Dwivedi, R. K.; Shukla, S. K.; Shukla, C. P.; Misra, P. K.; Seth, M. K. (Ecoprint: An International Journal of Ecology, 2009)
The present paper deals with 37 taxa, 18 genera, 32 species, 4 varieties and 1 forma explored from southern Himanchal Pradesh of India. These taxa are represented by Microcystis, Chroococcus, Aphanocapsa, Aphanothece, Merismopedia, Coelosphaerium, Gomphosphaeria, Stichosiphon, Oscillatoria, Lyngbya, Pseudanabaena, Cylindrospermum, Anabaena, Nostoc, Nodularia, Fortiea, Calothrix, Anabaenopsis. Out of 37 taxa, 27 are first report from the study area. Key words: Fresh-water, blue-green algae, systematics, southern Himanchal Pradesh, India. doi: 10.3126/eco.v15i0.1939 ECOPRINT 15: 29-36, 2008